2021
DOI: 10.4103/jpbs.jpbs_295_21
|View full text |Cite
|
Sign up to set email alerts
|

To Compare the Accuracy of 0.022 Inch Slot of Stainless Steel and Ceramic Orthodontic Brackets Marketed by Different Manufacturers

Abstract: Aim of the Study: The aim of the present study was to analyze the accuracy of 0.022 inch slot of stainless steel and ceramic orthodontic brackets marketed by different manufacturers. Materials and Methods: An in vitro study was done on upper left central incisor bracket of MBT 0.022 slot of American orthodontics (AO), 3M Unitek, Ormco with each 20 of stainless steel and ceramic brackets divided into six groups, and the total sample was 120. The brackets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…unit standardization; they are among the researchers who have defined the spectrum of slot and archwire manufacturing features. [ 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…unit standardization; they are among the researchers who have defined the spectrum of slot and archwire manufacturing features. [ 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 ]…”
Section: Introductionmentioning
confidence: 99%
“…These comprise leaf gauges, pin gauges, digital gauges, a profile projector microscope, a stereomicroscope, an optical microscope, a scanning electron microscope, and a micro-CT scanner. [ 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 ]…”
Section: Introductionmentioning
confidence: 99%
“…According to our previous results on XRD [20], peaks of C and TiC were observed in both the TiCN and Ti-DLC films, but the latter was more pronounced, indicating that According to our previous results on XRD [20], peaks of C and TiC were observed in both the TiCN and Ti-DLC films, but the latter was more pronounced, indicating that more TiC was formed. From our previous experimental results of Raman spectroscopy [20], the response intensity for sp 2 -hybridized C in Ti-DLC films was approximately 50 times higher than that for sp 3 -hybridized C. It was found that a certain amount of sp 3 -hybridized C was present in the Ti-DLC films, and the D peak area was significantly larger than the G peak area (ID/IG = 2.79). This indicates that the proportion of sp 2 -hybridized C was higher than that of sp 3 -hybridized C.…”
Section: Surface Characteristicsmentioning
confidence: 90%
“…more TiC was formed. From our previous experimental results of Raman spectroscopy [20], the response intensity for sp 2 -hybridized C in Ti-DLC films was approximately 50 times higher than that for sp 3 -hybridized C. It was found that a certain amount of sp 3 -hybridized C was present in the Ti-DLC films, and the D peak area was significantly larger than the G peak area (ID/IG = 2.79). This indicates that the proportion of sp 2 -hybridized C was higher than that of sp 3 -hybridized C.…”
Section: Surface Characteristicsmentioning
confidence: 90%
See 1 more Smart Citation